3D Ex vivo tissue platforms to investigate the early phases of influenza a virus- and SARS-CoV-2-induced respiratory diseases. Issue 1 (31st December 2022) - Schloer, Sebastian; Treuherz, Daniel; Faist, Aileen; de Witt, Marlous; Wunderlich, Katharina; Wiewrodt, Rainer; Wiebe, Karsten; Barth, Peter; Wälzlein, Joo-Hee; Kummer, Susann; Balkema-Buschmann, Anne; Ludwig, Stephan; et al.
ABSTRACT: Pandemic outbreaks of viruses such as influenza virus or SARS-CoV-2 are associated with high morbidity and mortality and thus pose a massive threat to global health and economics. Physiologically relevant models are needed to study the viral life cycle, describe the pathophysiological consequences of viral infection, and explore possible drug targets and treatment options. While simple cell culture-based models do not reflect the tissue environment and systemic responses, animal models are linked with huge direct and indirect costs and ethical questions. Ex vivo platforms based on tissue explants have been introduced as suitable platforms to bridge the gap between cell culture and animal models. We established a murine lung tissue explant platform for two respiratory viruses, influenza A virus (IAV) and SARS-CoV-2. We observed efficient viral replication, associated with the release of inflammatory cytokines and the induction of an antiviral interferon response, comparable to ex vivo infection in human lung explants. Endolysosomal entry could be confirmed as a potential host target for pharmacological intervention, and the potential repurposing potentials of fluoxetine and interferons for host-directed therapy previously seen in vitro could be recapitulated in the ex vivo model.